INOVASI PENGOLAHAN OTAK-OTAK IKAN PATIN PADA UMKM â€œAHMADI KULINERâ€ - Iriani, Dian; Hasan, Bustari; Alfajriey, Rayhand; Ramadhan, Tengku Rahmat; Zein, Fauzan Fadilah; Sidik, Fawwaz Afifah; Berkhaty, Ayang Putri; Ananda, Dea; Maulani, Iffah; Rinanda, Khairunnisa Yulia; Yustiani, Maulida (Universitas Mataram, 2023)
Ahmadi Culinary MSME is one of the MSMEs in Pulau Lawas Village, Bangkinang District, Kampar which has great potential in developing local community businesses by utilizing catfish which is the mainstay fish of this Regency. The aim of this activity is to help Ahmadi Culinary MSME partners in Pulau Lawas village by providing training in innovation in developing new products made from catfish in the form of grilled fish cake (otak-otak ikan) as a healthy food. The method used in this activity was counseling about the benefits of consuming fish meat and continued with training in making grilled fish cake as a new innovation in developing healthy snack products. Before the activity is carried out, participants who are MSME partners fill out a questionnaire (Pre-test) and are asked for their opinion about the product that has been made (Post-test). Data collection was carried out qualitatively and discussed in accordance with the literatures. The outreach and training activities at Ahmadi Culinary MSME ran successfully where participants were very enthusiastic about innovating to develop new products made from local ingredients in the form of grilled fish cake as a healthy snack. The increasing in partners' knowledge is 85% from initially not understanding enough, to being very understanding and able to make its product with attractive shapes, good taste and good packaging. By developing grilled fish cake products, it is hoped that partners can expand the marketing area, not only in areas around villages and districts but also up to the provincial level and even the national level. So with innovation in the development of new products in the form of grilled fish cake, Ahmadi Kuliner MSME partners can add new culinary variants, which are expected to increase the economic income of partner members.